2022
DOI: 10.1038/s41591-022-01789-0
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab versus tocilizumab in rheumatoid arthritis: synovial biopsy-based biomarker analysis of the phase 4 R4RA randomized trial

Abstract: Patients with rheumatoid arthritis (RA) receive highly targeted biologic therapies without previous knowledge of target expression levels in the diseased tissue. Approximately 40% of patients do not respond to individual biologic therapies and 5–20% are refractory to all. In a biopsy-based, precision-medicine, randomized clinical trial in RA (R4RA; n = 164), patients with low/absent synovial B cell molecular signature had a lower response to rituximab (anti-CD20 monoclonal antibody) compared with that to tocil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 52 publications
6
129
0
1
Order By: Relevance
“…On the contrary, the lack of response to both drugs was associated with more than 1000 genes. Interestingly, the fibroid pauci-immune pathotype was associated with a poor response to the drugs, supporting the hypothesis that pauci-immune phenotype represents a refractory endotype [11].…”
supporting
confidence: 58%
“…On the contrary, the lack of response to both drugs was associated with more than 1000 genes. Interestingly, the fibroid pauci-immune pathotype was associated with a poor response to the drugs, supporting the hypothesis that pauci-immune phenotype represents a refractory endotype [11].…”
supporting
confidence: 58%
“…We do not have a handle yet of the immunopathogenic characterisation of recalcitrant disease although data are emerging 30. It is beyond the scope of this article to discuss the potential biological basis of D2T-RA and within this, refractory RA, which has been discussed previously 18.…”
Section: Current Concept Of D2t Ramentioning
confidence: 98%
“…Identifying the basis for D2T-RA We do not have a handle yet of the immunopathogenic characterisation of recalcitrant disease although data are emerging. 30 It is beyond the scope of this article to discuss the potential biological basis of D2T-RA and within this, refractory RA, which has been discussed previously. 18 Stratification according to the presence and absence of inflammation would be an important first step and align with the EULAR PtC.…”
Section: Key Factors To Consider In the Management Of D2t-ramentioning
confidence: 99%
“…Empowered by the progress of next generation sequencing (NGS) technologies, genomic assays are currently being used to search for molecular patterns that can stratify patients' lesions beyond standard histological assays. Genomic assays that include transcriptomic information contributed to the identification of several molecular signatures of IMIDs, some of which have been successfully correlated to distinct clinical outcomes (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Strategies profiling tissues in bulk only inform on the average expression profile of a mixture of different cell types and cannot resolve cell-specific gene expression programs (49).…”
Section: High Dimensional Single-cell Technologies: Enhancing Immunop...mentioning
confidence: 99%
“…Patients with a low or absent B-cell lineage expression signature in synovial tissue better responded to the IL-6 receptor antagonist tocilizumab, than to B-cell depleting rituximab ( 73 ). Ancillary analyses in a follow-up study further revealed that humoral immune response gene signatures associated with response to rituximab and tocilizumab, while patients with a stromal/fibroblast signature were refractory to all medications ( 41 ). Overall, these studies thus emphasize the importance of including molecular signatures into clinical algorithms to improve the usage of available biotherapies and guide drug development priorities for refractory patients.…”
Section: Introductionmentioning
confidence: 99%